PERIPROCEDURAL MYOCARDIAL DAMAGE - S. A. Akinina (Кардиоваскулярная терапия и профилактика, 2013)
Percutaneous coronary intervention (PCI), as a method of myocardial revascularisation, is widely and effectively used for the treatment of coronary heart disease (CHD), with immediate success rates of >90%. Depending on the diagnostic criteria, 5–30% of these patients could develop the signs of periprocedural myocardial damage (PMD) or periprocedural myocardial infarction (PMI). PMD predictors, mechanisms of PMD development, and its specific clinical features play an important role in the PMI prevention. At present, there is no universal agreement on the definition and diagnostics of periprocedural myocardial necrosis and PMI, or on their impact on the clinical outcomes. According to the results of the recent studies, which are presented in this review, the current criteria of PMI might need to be modified, due to the increasingly high sensitivity of the modern threshold levels of troponin.